A systematic literature review of incidence, mortality, and relapse of patients diagnosed with chronic graft versus host disease. Issue 5 (4th May 2019) - Csanadi, Marcell; Agh, Tamas; Tordai, Attila; Webb, Thomas; Jeyakumaran, Dusha; Sengupta, Nishan; Schain, Frida; Mattsson, Jonas
ABSTRACT: Introduction : Chronic graft-versus-host disease (chronic GVHD) is a leading cause of late death and contributes significantly to morbidity following hematopoietic stem cell transplantation. This study aims to provide a systematic literature review on incidence, mortality, and relapse of chronic GVHD patients. Areas covered : The authors searched for English-language articles published between 2007 and 2017 using PubMed. Studies that applied the 2005 or 2015 NIH Consensus Criteria for the diagnosis and staging of chronic GVHD, and had a cohort size of at least 100 patients were included. Expert opinion : The authors found a wide variation of incidence rates, which can be explained by heterogeneity in the characteristics of study samples and applied transplantation protocols. Chronic GVHD was associated with higher non-relapse mortality (NRM), superior overall survival (OS) and lower risk of relapse. Studies indicated an increased risk for NRM and worse OS in the presence of more severe disease. Future therapies should focus to reach a delicate balance between controlling disease severity among patients diagnosed with chronic GVHD and preserving the graft versus tumor effect which goes along with chronic GVHD and results in improved OS and decreased relapse rate. Nonetheless, factors predicting disease severity still need to be further understood.